Effect of Increasing Occlusal Vertical Dimension on Smile Parameters - Pahari, S; Pradhan, S Joshi; Shrestha, P; Sah, S; Verma, A (Journal of Nepalese Prosthodontic Society, 2023)
Introduction: Increasing Occlusal Vertical Dimension (OVD) becomes important aspect of complex prosthodontic treatment for maintaining balance between form of oral structures and function of stomatognathic system. The purpose of this study is to determine the effect of increasing OVD on various smile parameters during posed smile.Methodology: This observational descriptive study included 30 patients, 14 male and 16 females, visiting dental department of National Academy of Medical Sciences (NAMS), Bir Hospital. Four polyvinyl siloxane bite records were fabricated on stone cast mounted on a semi-adjustable articulator increasing OVD by +1 mm, +2 mm, +3 mm and +4 mm taking incisal pin as a reference. Photographs of posed smile were taken at OVD of +0 mm, +1 mm, +2 mm, +3 mm and +4 mm using a DSLR camera mounted on a tripod. Head position was stabilized using a head positioning device of a cephalometric unit during photography. Adobe photoshop CS6 extended was used to calculate the various measurement in pixel which was converted into mm with help of conversion ratio obtained. Data were then processed and analyzed using SPSS software at the 5 % significance level.Result: One-way repeated measures ANOVA found statistically significant differences in interlabial gap height, incisal edge to lower lip distance, smile index and display zone area with increasing OVD. No statistically significant differences were found for intercommisural width and incisal edge to upper lip distance.Conclusion: Within the limitations of this study, the excessive increase of OVD may lead to excessive interlabial gap height, incisal edge to lower lip distance, and display zone area. Also, the increase of OVD may lead to reduced smile index. No change may be expected in the position of the upper lip with increase of OVD. In addition, a change in the intercommisural width of the smile should not be expected with increasing OVD.